Kajian Yuridis Badan Bank Tanah dalam Hukum Agraria Indonesia - Kafrawi; Rachman Maulana Kafrawi (Faculty of Law Hang Tuah University, 2022)
The problem of land acquisition is a problem that always arises in development activities. The emergence of land speculators who take advantage of the project infrastructure development. In the end, this causes development projects to be difficult to implement, and even fail or be abandoned altogether. Therefore, in Law Number 11 of 2020 concerning Job Creation, the government establishes a land bank agency that functions as land manager. The result of this research is that the existence of a land bank agency has existed both constitutionally in the Indonesian agrarian law system, namely in Article 33 Paragraph (3) of the 1945 Constitution, which is then implicitly enshrined in Article 2 paragraph (2) of the UUPA. The land bank agency is a form of authority of the State Controlling Rights over Land (HMN) which carries out the function as land manager. The regulation of land bank entities in Law Number 11 of 2020 concerning Job Creation places investment as a top priority, in addition to several other objectives, such as public interests, social interests, national development interests, economic equity, land consolidation and agrarian reform. This is different from the concept of land banks in several other countries, such as the Netherlands, Sweden and the United States, which are broadly focused on welfare. The implementation of land banks in these countries is very dependent on the needs of the community in a particular area, because that will determine the objectives and focus of the land bank specifically.